The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1158/0008-5472.can-22-2449
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine Promotes Translation of VEGFA to Accelerate Angiogenesis in Lung Cancer

Abstract: Angiogenesis is hijacked by cancer to support tumor growth. RNA modifications such as N6-methyladenosine (m6A) can regulate several aspects of cancer, including angiogenesis. Here, we find that m6A triggers angiogenesis in lung cancer by upregulating vascular endothelial growth factor-A (VEGFA), a central regulator of neovasculature and blood vessel growth. m6A-sequencing and functional studies confirmed that m6A modification of the 5’UTR of VEGFA positively regulates its translation. Specifically, methylation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…[ 11 ] The m 6 A site at IRES‐A suppresses uORF impairment while facilitating G‐quadruplex‐induced translation of VEGFA in lung cancers. [ 52 ] In the current study, we found that the mRNA expression of VEGFA was upregulated by YTHDF2 via ETV5 in HCC. These results indicate that the network by which YTHDF2 regulates the expression of VEGFA in different tumor cell backgrounds is complex.…”
Section: Discussionmentioning
confidence: 53%
“…[ 11 ] The m 6 A site at IRES‐A suppresses uORF impairment while facilitating G‐quadruplex‐induced translation of VEGFA in lung cancers. [ 52 ] In the current study, we found that the mRNA expression of VEGFA was upregulated by YTHDF2 via ETV5 in HCC. These results indicate that the network by which YTHDF2 regulates the expression of VEGFA in different tumor cell backgrounds is complex.…”
Section: Discussionmentioning
confidence: 53%
“…VEGFA binds to VEGFR2 on the surface of endothelial cells to stimulate the AKT-mTOR downstream signaling pathway, thereby exerting its biological functions, such as angiogenesis and vascular permeability ( 20 , 32 , 33 ). VEGFA is upregulated in NSCLC tissues and has been associated with an increased risk of recurrence, metastasis, and death of patients with NSCLC ( 34 ). Hence, we further detected the VEGFA levels in the CM derived from NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, Orn augmented VEGF-A expression by enhancing the mRNA stability of VEGF-A. N6-methyladenosine (m6A) modification, one of the most common modifications of mRNAs [ 43 ], was previously shown to boost the translation of VEGF-A to accelerate angiogenesis [ 44 ], suggesting m6A modification might be involved in the process of Orn in modulating VEGF-A mRNA stability, though this mechanism warrants further investigation. The above-described indicated that Orn promotes placental angiogenesis through regulating VEGF-A.…”
Section: Discussionmentioning
confidence: 99%